Kesan Saliniti dan Keamatan Cahaya ke atas Pertumbuhan Chiorella virginica - Alias, Abdullah Zaini (1988)
A study on the effects of salinity and light intensity on the growth of Chlorella virginica was conducted in an environmental control room at a temperature of 22 ±;Pc. Salinities were set at 15 ppt, 20 ppt, 25 ppt and 30 ppt while light intensities were at 1140 lux, 2260 lux and 3040 lux. The effect of salinity and light intensity was found to be significantly different (P <0. 01 - 0.05). Optimum salinity for the growth of Chlorella virginica was at 15 ppt whilst optimum light intensity was at 3040 lux. Interaction between salinity and light intensity was also significantly different (P <0.01 - 0.05) whereby maximum growth (39375 cells/pJ) was obtained at a salinity of 15 ppt and light intensity of 3040 lux.